Pengaruh Lama Pemeraman Buah terhadap Perkembangan Mutu Benih Tomat (Solanum lycopersicum L.) - Adevia Triyani Br Munthe; Anak Agung Made Astiningsih; Ni Nyoman Ari Mayadewi (Fakultas Pertanian, Universitas Udayana, 2022)
This study aims to determine the effect of ripening time on the development of tomato seed quality. The experiment used was a Completely Randomized Design (CRD) one, namely the ripening time. Design with 5 treatment factors: ripening stage tomatoes (redness less than 10%) without ripening (Control), 2 days ripening (P1), 4 days ripening (P2), 6 days ripening (P3), 8 days ripening (P4). Observations were made on the variables of moisture content, weight of 1000 grains, germination and seed germination spirit simultaneously. The results showed that the time of fruit ripening had a significant effect on the development of tomato quality (physical and physiological quality of seeds). The highest seed moisture content was obtained from the control treatment, which was 49,50% then along with the ripening time of the fruit and the weight of 1000 seeds was constant. The ripening stage of broken tomatoes for 6 days resulted in the highest vigor and viability, respectively 89,66% and 86,26%.